Uarda : a Romance of Ancient Egypt $1 (BVolume 01s - Ebers, Georg, 1837-1898; Bell, Clara, 1834-1927 (Salt Lake City, UT : Project Gutenberg, 2004)
"Uarda: A Romance of Ancient Egypt $1 (BVolume 01" by Georg Ebers is a historical novel written in the late 19th century. Set against the backdrop of ancient Egypt, the story intricately explores the lives of individuals amidst the cultural and political milieu of the time. The narrative begins with significant references to historical events and archaeological details, which suggest a deep concern for authenticity, though it ultimately prioritizes storytelling over strict historical accuracy. The opening of the novel introduces us to the City of the Dead in Thebes, vividly described with lush imagery of the Nile and the contrasting barrenness of the surrounding desert. Here we meet key characters, including Bent-Anat, the daughter of Pharaoh, who inadvertently injures a girl from a lower social class while driving her chariot. This event sets off a chain of interactions among the nobility and the lower classes, particularly involving Bent-Anat's quest for redemption as she seeks help for the injured girl. The dynamics between high-ranking individuals and commoners start to manifest, hinting at themes of class struggle and the complexities of human emotion within the societal structures of ancient Egypt. The protagonist's journey appears to be one of moral reckoning, as we see the rich tapestry of life interwoven with personal and societal challenges in this ancient civilization. (This is an automatically generated summary.)s
Release date is 2004-04-01
This eBook was produced by David Widger
Keywords: Egypt -- History -- To 332 B.C. -- Fiction; German fiction -- Translations into English